Does aid mitigate external shocks? - Collier, P; Goderis, B (Centre for the Study of African Economies, 2007)
This paper investigates the role of aid in mitigating the adverse effects of commodity export price shocks on growth in commodity-dependent countries. Using a large cross-country dataset, we find that negative shocks matter for short-term growth, while the ex ante risk of shocks does not seem to matter. We also find that both the